Emergency department presentations for atrial fibrillation and flutter in Alberta: a large population-based study. Issue 1 (December 2016) - Rosychuk, Rhonda; Graham, Michelle; Holroyd, Brian; Rowe, Brian
Abstract Background Atrial fibrillation or flutter (AFF) are not infrequent presenting problems in Emergency Departments (ED); however, little is known of the pattern of these presentations. This study provides a description of AFF presentations and outcomes after ED discharge in Alberta. Methods Provincial administrative databases were used to obtain all primary ED encounters for AFF during 1999 to 2011 for patients aged >35 years. Data extracted included demographics, ED visit timing, and subsequent visits to non-ED settings. Analysis included summaries and standardized rates. Results During the study period, there were 63, 398 ED AFF visits from 32, 104 distinct adults. Median ages for females and males were 75 and 67 years, respectively; more men (52%) and patients > 65 presented. Overall, the standardized rates remained similar (2.8 per 1, 000 over the study period). Specific populations of human services recipients and First Nations had higher ED visit rates for AFF than other groups. Predictable daily, weekly, and monthly trends were observed. The ED visits were followed by numerous subsequent visits in non-ED settings; however, First Nations and women had lower rates of specialist follow-up. Conclusions Annually, over 5, 000 ED presentations of patients experiencing AFF occur in Alberta and admissions proportions are declining. While presentation rates across the province are stable, follow-up with physicians, consultation with cardiologists and health outcomes vary based on socio-economic, age, sex, and First Nations status. Further research is required to understand the causes and consequences of these inequalities and to standardize care.